A Competitive Study of the Static and Fatigue Performance of Flax, Glass, and Flax/Glass Hybrid Composites on the Structural Example of a Light Railway Axle Tie - Graupner, Nina; Hohe, Jörg; Schober, Michael; Rohrmüller, Benedikt; Weber, David; Bruns, Lisa; Bruns, Albert; Müssig, Jörg (Frontiers in Materials, 2022)
The most common studies in the literature are those analysing fatigue life under cyclic loading for flax fibre reinforced composites. A novel type of staple fibre yarn made from flax tow with almost unidirectional fibre orientation and a quasi-unidirectional fabric was developed for composite applications. Additionally, a hybrid material made of flax and glass was produced for a demonstrator component (axle tie of a narrow-gauge railway). For such an application, the investigation of fatigue strength is of particular importance. Therefore, the fatigue behaviour of flax, glass and hybrid flax/glass composites was investigated in the high cycle fatigue (HCF) range. A total of 10^6 load cycles were carried out. From about 7³ to 8³ loading cycles, the flax laminate was found to have higher fatigue strength than the glass fibre-reinforced composite. The hybrid materials tend to show a higher fatigue strength than the glass type from approximately 2*10^5 load cycles. Results based on a finite element method have also demonstrated better fatigue properties at an increased number of load cycles for flax-based composites than the glass fibre-reinforced component. The flax/glass component's fatigue strength ranged between the flax values and the glass fibre-reinforced composites. Overall, the hybrid material shows significantly better static bending and impact characteristics than flax and considerably better fatigue properties than the glass fibre-reinforced composite making the hybrid material attractive for an application in an axle tie.